2012
DOI: 10.1117/12.914800
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of internal gain, dark current and cutoff wavelength of UV photodetectors using quasi-alloy of BGaN-GaN and BGaN-AlN superlattices

Abstract: Metal-semiconductor-metal solar blind ultraviolet photodetectors have been fabricated using both BGaN-GaN and BGaN-AlN superlattices as active layers. A high internal gain (up to 3 × 10 4 for optical power in the nW range) is obtained with a highly reduced dark current thanks to the boron incorporation. In the high optical power regime (W range), the time response is in the nanosecond range, which is much smaller than that of GaNand ZnO-based ultraviolet photodetectors. Moreover, the boron incorporation in GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…6 for dark/light pulses of 20 s and 10 s, at the moment when the light was switched on and off, the measured current has a steep change reaching a photoconductivity yield of around 100 ± 20%. Following that, a slow increase or decay component was observed which was caused by trapping/detrapping processes of the carriers at deep levels in the bandgap of the material 2931 .
Figure 6Response of prototypical thick BN-based photodetector (applied voltage of 100 V) under dark/light cycles ( a ) with pulse time of 20 s and ( b ) with pulse time of 10 s.
…”
Section: Resultsmentioning
confidence: 99%
“…6 for dark/light pulses of 20 s and 10 s, at the moment when the light was switched on and off, the measured current has a steep change reaching a photoconductivity yield of around 100 ± 20%. Following that, a slow increase or decay component was observed which was caused by trapping/detrapping processes of the carriers at deep levels in the bandgap of the material 2931 .
Figure 6Response of prototypical thick BN-based photodetector (applied voltage of 100 V) under dark/light cycles ( a ) with pulse time of 20 s and ( b ) with pulse time of 10 s.
…”
Section: Resultsmentioning
confidence: 99%
“…The absence of any increase in the XRD intensity suggests that the additional thickness does not contribute to the (0001)-oriented wurtzite phase that first nucleates on the template. Since the (111) zinc-blende and (0002) wurtzite peaks for GaN occur at nearly identical angles in the symmetric diffraction geometry, pole figures were performed near the (311) zinc blende and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) wurtzite GaN reflections to determine possible changes to the BGaN phase as the film thickness is increased. Furthermore, the presence of six-fold rotational symmetry for both reflections points to the presence of twins within the cubic-phase domains of the BGaN film.…”
Section: Identification Of Wurtzite-to-cubic Phase Transitionmentioning
confidence: 99%
“…Nonetheless, some groups have achieved higher boron compositions with quantum well or superlattice structures by using pulsed growth techniques or through the use of BAlN or BAlGaN alloys. [7,8,[15][16][17] In this study, we explore boron incorporation in BGaN under wide-ranging growth conditions and report on the resulting surface morphology and crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages for MSM structures are the possibility (i) to achieve self-powered operation similar to that demonstrated for UV photodetectors either by using two different metal contacts or the same contacts with specific metal semiconductor interface engineering 15 17 and (ii) to benefit from internal gain to increase the neutron response signal. 18 , 19 McGregor et al 20 have demonstrated for the first time the feasibility of pyrolytic BN-based neutron detectors with an efficiency of up to 7.2% under an electric field of 4 kV/cm. More recently, neutron detectors have been demonstrated with epitaxial monocrystalline h-BN using natural and enriched 10 B with different thicknesses up to 50 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages for MSM structures are the possibility (i) to achieve self-powered operation similar to that demonstrated for UV photodetectors either by using two different metal contacts or the same contacts with specific metal semiconductor interface engineering 15−17 and (ii) to benefit from internal gain to increase the neutron response signal. 18,19 McGregor et al 20 B with different thicknesses up to 50 μm. 21−24 These promising results by the group at Texas Tech University (TTU) suggest that more research would be needed to further explore the benefit of h-BN MSM detectors.…”
Section: Introductionmentioning
confidence: 99%